Chronic rhinosinusitis and sleep quality. Issue 1 (February 2020) - Papagiannopoulos, Peter; Kuan, Edward C.; Tajudeen, Bobby A.
Abstract : Purpose of review: To review the recent literature describing the association between chronic rhinosinusitis and its effects on sleep quality. Recent findings: Chronic rhinosinusitis (CRS) causes significantly worse sleep by both subjective and objective measures. CRS is also strongly associated with obstructive sleep apnea. Treating CRS surgically improves subjective sleep scores. Summary: CRS worsens sleep quality both subjectively and objectively. Sleep quality is improved after endoscopic sinus surgery.